2019
DOI: 10.1002/ptr.6327
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyprenols reduce demyelination and recover impaired oligodendrogenesis and neurogenesis in the cuprizone murine model of multiple sclerosis

Abstract: Recent studies showed hepatoprotective, neuroprotective, and immunomodulatory properties of polyprenols isolated from the green verdure of Picea abies (L.) Karst . This study aimed to investigate effects of polyprenols on oligodendrogenesis, neurogenesis, and myelin content in the cuprizone demyelination model. Demyelination was induced by 0.5% cuprizone in CD‐1 mice during 10 weeks. Nine cuprizone‐treated animals received daily injections of polyprenols intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
2
7
0
1
Order By: Relevance
“…However, short-term cessation of blood flow leads to serious damage to only certain brain regions. A distinctive feature of the global ischemia-hypoxia model in rodents is severe damage to the hippocampal pyramidal neurons in the CA1 field [ 13 , 14 , 31 , 34 ], which is confirmed by the results of our previous [ 17 , 19 , 35 ] and present studies. In addition, a number of studies have found damage to the neurons of the cerebellum, cortex, striatum and thalamus in global ischemia-hypoxia [ 36 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, short-term cessation of blood flow leads to serious damage to only certain brain regions. A distinctive feature of the global ischemia-hypoxia model in rodents is severe damage to the hippocampal pyramidal neurons in the CA1 field [ 13 , 14 , 31 , 34 ], which is confirmed by the results of our previous [ 17 , 19 , 35 ] and present studies. In addition, a number of studies have found damage to the neurons of the cerebellum, cortex, striatum and thalamus in global ischemia-hypoxia [ 36 , 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Myelin content in the hippocampal layers was assessed in ROIs similar to those for calculation of NeuN+, GFAP+, Iba1+, NG2+, CNP+ cells in the layers SO, SP, SR, SL and SE near the CA1 field ( Figure 6 ). Assessment was performed using the Otsu thresholding method in the ImageJ (National Institutes of Health, Bethesda, MD, USA) implementation as a percent of MBP-positive area [ 35 , 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, nonpharmacological treatments are being increasingly recognized as valuable adjunct interventions when designing comprehensive neuroregenerative therapies. 88,89 Exercise, socialization, and nutritional modifications demonstrated both neuroprotective and regenerative effects in animal models of MS [55][56][57]90,91 (Tables 7 and 8), and the many beneficial effects of plant-derived organic compound formulations [24][25][26][92][93][94][95] further supports integrating dietary modifications into MS treatment regimens. Although many non-pharmacological strategies are multifactorial, and are therefore more difficult to evaluate for direct effects on specific outcomes in individuals with MS, their minimal associated risks and practical ease of implementation are attractive features for use in the management of MS.…”
Section: Discussionmentioning
confidence: 99%
“…While the GG genotype of rs222747 is linked to enhanced glutamate transmission in the brain ( Mori et al., 2012 ), MS patients carrying this genotype are known to display exacerbated symptoms ( Buttari et al., 2017 ), even though the same SNP seems to reduce TNFα cytokine expression in the CSF which has been proposed to alleviate the disease ( Taoufik et al., 2011 ). Furthermore, insights from mouse models of MS suggest that while the inflammatory environment of the brain may enhance proliferation of HPCs during the acute phase ( Giannakopoulou et al., 2013 , 2017 ), the number of proliferating cells and immature neurons is likely to fall as the disease progresses ( Guo et al., 2010 ; Khodanovich et al., 2019 ; Zhang et al., 2020 ). Taken together, the GG genotype of rs222747 is more likely to contribute to the vulnerability of HPC0A07/03C cells to excitotoxicity generated by elevated glutamate levels, despite reduced TNFα production due to the same genotype.…”
Section: Variants With Demonstrated Effects On Gene or Cellular Levelmentioning
confidence: 99%